1999
DOI: 10.1001/archotol.125.3.314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Functional Endoscopic Sinus Surgery on Bronchial Asthma Outcomes

Abstract: The data do not support the hypothesis that first-time FESS for medically refractory chronic rhinosinusitis in adult patients with chronic asthma leads to reduced postoperative asthma symptoms or asthma medication use or improved pulmonary function. Based on this limited study, a reexamination of the benefits of sinus surgery to coexisting asthma is in order.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 17 publications
2
32
1
1
Order By: Relevance
“…These patients require intensive care during these attacks and these episodes are a marker of poor asthma control. Goldstein et al in a retrospective case study has shown reduction of these episodes after ESS [13]. We also had a marked reduction in visits to the emergency room/ casualty in our patients after surgery.…”
Section: Discussionsupporting
confidence: 67%
“…These patients require intensive care during these attacks and these episodes are a marker of poor asthma control. Goldstein et al in a retrospective case study has shown reduction of these episodes after ESS [13]. We also had a marked reduction in visits to the emergency room/ casualty in our patients after surgery.…”
Section: Discussionsupporting
confidence: 67%
“…However, they did not use any objective assessments such as pulmonary function tests. By contrast, Goldstein et al [23] found that ESS did not reduce postoperative asthma symptoms or asthma medication use, or result in improved pulmonary function. They studied a small number of subjects who had severe nasal polyposis and allergy prior to surgery and they did not evaluate objective sinonasal outcomes after ESS.…”
Section: Discussionmentioning
confidence: 96%
“…Radiological studies have shown abnormal sinus radiographs in 53% [2,3] and mucosal thickening on sinus computed tomography (CT) scans in 74% [4] of patients with asthma. Recently, .84% of CT scans were found to be abnormal in severe asthma, with a correlation between the extent of CT changes, sputum eosinophilia and pulmonary function [5].A number of authors have investigated the effect of surgical treatment of rhinosinusitis upon asthma, with improvement [6-8], worsening [9, 10] and equivocal effect [11,12] being reported. Only two studies of medical chronic rhinosinusitis (CRS) treatment exist, one included four medical patients [13], whereas the other considered CRS with polyposis alone and was nonrandomised [14].…”
mentioning
confidence: 99%
“…A number of authors have investigated the effect of surgical treatment of rhinosinusitis upon asthma, with improvement [6][7][8], worsening [9,10] and equivocal effect [11,12] being reported. Only two studies of medical chronic rhinosinusitis (CRS) treatment exist, one included four medical patients [13], whereas the other considered CRS with polyposis alone and was nonrandomised [14].…”
mentioning
confidence: 99%